Fundamentalisme Agama Sebagai Tantangan Bagi Negara - Mathias Daven (Institut Filsafat dan Teknologi Kreatif Ledalero, 2016)
The 16 th Century Protestant Reformation, triggered by Martin Luther and fellow reformers, eventually resulted in violent conflicts between various Church movements and their individual political supporters. These conflicts brought about a new awareness in the European peoples of the time, that the moralization of politics based on the truth of one religious group/Church always represents a clear threat to the life of a pluralistic society. The function of state politics is to guarantee life in peace together, with freedom and justice, among people who have differing religious convictions and who wish to establish a country together. On the contrary, religious fundamentalism is the greatest enemy of a country in so far as it attacks the principle of state secularism and fights for a return to state politics as an issue of “right or wrong”. To the extent that fundamentalism rejects the autonomy of the political system and enforces without compromise its own absolute truth on others, it is a clear threat to peace. Keywords: Reformation, Church, Fundamentalism, State, Politics, Truth, Peace ——————————————————————————————————————— Reformasi Protestan pada abad XVI yang dipelopori Martin Luther dengan kawan-kawan berujung pada konflik peperangan antargereja yang berbeda dan masing-masing pendukung politisnya. Konflik tersebut memunculkan kesadaran baru dalam masyarakat modern Eropa kala itu bahwa moralisasi politik berdasarkan kebenaran iman suatu agama selalu merupakan ancaman nyata bagi kelangsungan masyarakat yang heterogen. Tugas politik kenegaraan ialah menjamin hidup bersama secara damai dalam kebebasan dan keadilan dari orang-orang yang mempunyai latar belakang keagamaan dan keyakinan yang berbeda dan bertekad membangun suatu negara bersama. Sebaliknya fundamentalisme agama merupakan musuh utama negara sejauh ia melabrak prinsip sekularitas negara serta mengembalikan politik kenegaraan sebagai perihal “benarsalah”. Sejauh fundamentalisme menolak otonomi sistem politik dan memaksakan tanpa kompromi kebenaran absolut yang diyakini pada pihak lain, ia merupakan ancaman nyata bagi perdamaian. Kata-kata kunci: Reformasi, Gereja, Fundamentalisme, Negara, Politik, Kebenaran, Perdamaian